Sarala Devi Chaudhurani - Mitra, Rakhi (Kolkata Institute of Social and Cultural Studies, 2018)
01 black and white illustration
Notes and references, bibliography
Keywords: Biography- Sarala Devi Chaudhurani; Nationalists- India- Bengal- Biography; Women social reformers- India- Bengal- Biography